Single‐Molecule Ex Situ Atomic Force Microscopy Allows Detection of Individual Antibody–Antigen Interactions on a Semiconductor Chip Surface. Issue 2 (18th December 2020) - Lu, Ming-Pei; Weng, Ying-Ya; Yang, Yuh-Shyong
Abstract : Although in situ atomic force microscopy (AFM) allows single‐molecule detection of antibody–antigen binding, the practical applications of in situ AFM for disease diagnosis are greatly limited, due to its operational complexity and long operational times, including the execution time for the surface chemical/biological treatments in the equipped glass liquid cell. Herein, a method of graphically superimposed alignment that enables ex situ AFM analysis of an immobilized antibody at the same location on a semiconductor chip surface before and after incubation with its antigen is presented. All of the required chemical/biological treatments are executed feasibly using standard laboratory containers, allowing single‐molecule ex situ AFM detection to be conducted with great practicality, flexibility, and versatility. As an example, the analysis of hepatitis B virus X protein (HBx) and its IgG antibody is described. Using ex situ AFM, individual information on the topographical characteristics of the immobilized single and aggregated IgG antibodies on the chip surface is extracted and the data are analyzed statistically. Furthermore, in a statistical manner, the changes in AFM‐measured heights of the individual and aggregated IgG antibodies that occur as a result of changes in conformation upon formation of IgG–HBx complexes are investigated. Abstract : An ex situ atomic force microscopy (AFM)–molecule chip technique integrated with a standard manufactured semiconductor chip and a graphically superimposed alignment technique allows the ex situ AFM analysis detection of antibody–antigen interactions at the single‐molecule level. This approach is significantly superior to conventional in situ AFM analysis detection in terms of its practicality, flexibility, and versatility.